2023
DOI: 10.3390/plants12061364
|View full text |Cite
|
Sign up to set email alerts
|

Nootropic Herbs, Shrubs, and Trees as Potential Cognitive Enhancers

Abstract: Plant-based nootropics are a diverse group of natural drugs that can improve cognitive abilities through various physiological mechanisms, especially in cases where these functions are weakened or impaired. In many cases, the nootropics enhance erythrocyte plasticity and inhibit aggregation, which improves the blood’s rheological properties and increases its flow to the brain. Many of these formulations possess antioxidant activity that protects brain tissue from neurotoxicity and improves the brain’s oxygen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 242 publications
0
6
0
Order By: Relevance
“…CA has been an important medicinal herb in traditional medicine used to improve cognition and memory but also to reduce anxiety and stress [ 12 , 45 ]. Although clinical trials that studied its effect on anxiety and depression have been very limited [ 17 ], antidepressant properties have been suggested by some studies in rodents that showed improvement in stress-induced behavior in rats and mice [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…CA has been an important medicinal herb in traditional medicine used to improve cognition and memory but also to reduce anxiety and stress [ 12 , 45 ]. Although clinical trials that studied its effect on anxiety and depression have been very limited [ 17 ], antidepressant properties have been suggested by some studies in rodents that showed improvement in stress-induced behavior in rats and mice [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the physiological and pharmacological actions of ginseng is nootropic [ 19 ]. There are two types of memory or cognition studies that have explored the effect of ginseng use on humans.…”
Section: Effects Of Ginseng Total Extract On Normal Young Adults or O...mentioning
confidence: 99%
“…In preclinical studies, Centella asiatica was also discovered to have antidepressant, anxiolytic, antistress, and seizure-prevention properties [182,183]. It has been shown to affect metabolic pathways connected to AD when administered to 5xFAD mice [184]. In rats overexpressed with β-amyloid, Centella asiatica extract has been demonstrated to enhance memory and decision-making, while it lowers hippocampus mitochondrial dysfunctioning.…”
Section: Gotu Kolamentioning
confidence: 99%
“…In rats overexpressed with β-amyloid, Centella asiatica extract has been demonstrated to enhance memory and decision-making, while it lowers hippocampus mitochondrial dysfunctioning. In a clinical investigation, a 70% water-ethanol extract of C. asiatica demonstrated promising anxiolytic properties by reducing anxiety and stress in patients [184].…”
Section: Gotu Kolamentioning
confidence: 99%